Gambaran Adaptabilitas Karir Karyawan Organisasi Retail - Eryandra, A; Sholihah, Maryam (Jurnal Ilmiah Penelitian Psikologi, 2024)
Changes in customer shopping behavior encourage companies engaged in the retail industry to make developments in the dynamics of their organizational work. To keep up with these changes and developments, employees of retail organizations must have adaptability which is implemented through career adaptability. This study aims to explain the description of career adaptability of employees of retail organizations. This study used a quantitative approach involving 408 employees of retail organizations in the Jabodetabek area. Data were collected online and offline through a questionnaire containing the Career Adapt-Abilities Scale (CAAS) measuring instrument adapted from Profeli & Savickas (2012) to measure employee career adaptability with a reliability value of 0.862. The results of empirical analysis show that the majority of retail organization employees' careers are in the moderate category with the level of career adaptability in the range of 85.63-102.07 with a percentage of 62.5%.